Gaya Kepemimpinan Kepala Madrasah untuk Meningkatkan Mutu Guru Pondok Pesantren Sabilul Mukminin Deli Serdang - Syafrizal, Syafrizal; Prasetia, Indra Prasetia; Amini, Amini (UMSU, 2025)
This research aims to understand the instructional and participative leadership styles of the Madrasah head in mobilizing the resources within an educational institution, viewed from academic standards and competency standards, which will be utilized to the fullest to achieve the following objectives: 1. To identify the instructional leadership style of the Madrasah head in improving teacher quality as seen from the academic standards of teachers at Pondok Pesantren Sabilul Mukminin Deli Serdang. 2.To identify the participative leadership style of the Madrasah head in improving teacher quality as seen from the academic standards at Pondok Pesantren Sabilul Mukminin - Deli Serdang.3.To identify the instructional leadership style of the Madrasah head in improving teacher quality as seen from the teacher competency standards at Pondok Pesantren Sabilul Mukminin - Deli Serdang. 4.To identify the participative leadership style of the Madrasah head in improving teacher quality as seen from the competency standards at Pondok Pesantren Sabilul Mukminin Deli Serdang. This research employs a qualitative research method and a case study approach, using data collection techniques such as observation, interviews, and documentation. The data sources for this research include the Madrasah head, foundation, deputy head of the Madrasah, teachers, and students. The results of the study indicate that the leadership style of the Madrasah head to improve teacher quality at Pondok Pesantren Sabilul Mukminin, as viewed from academic and competency standards, includes: 1. Conducting supervision activities, MGMP (Teacher Working Group), Classroom Action Research (CAR), training, and workshops as platforms for teachers to deepen their competencies and address teaching needs, as well as facilitating discussions between the Madrasah head and teachers. 2. Being involved in preparing ideas and innovations and deliberating with school officials. 3. Implementing a deliberative system, consistently prioritizing group interests, and attentively listening to and considering group opinions. 4. Facilitating infrastructure and resources, organizing MGMP activities, workshops, and motivating teachers, as well as providing training assistance/guidance to teachers according to their needs, where the instructional and participative leadership styles are used by the Madrasah head to carry out leadership functions.